Microbiological safety and stability of novel green sauces made with sea fennel (Crithmum maritimum L.). (July 2022) - Maoloni, Antonietta; Cardinali, Federica; Milanović, Vesna; Garofalo, Cristiana; Osimani, Andrea; Mozzon, Massimo; Aquilanti, Lucia
Graphical abstract: Highlights: Two new green sauces were developed using Crithmum maritimum L. as main ingredient. Two conventional and two mild pasteurization treatments were applied. Mild pasteurization treatments determined a complete elimination of S. aureus. An inhibition of the growth of B. cereus was seen during storage at 37 °C. Both sauces were shelf-stable during one month of storage at thermal abuse conditions. Abstract: Due to consumers' demand for ready-to-eat foods, in the last decades production of sauces has shifted from home-made to commercial practice. Besides to palatability and nutritional value, safety and stability are key issues of industrial sauces. The present study was aimed at evaluating the microbiological stability and safety of industrial-scale prototypes of two novel green sauces made with sea fennel ( Crithmum maritimum L.) as the main ingredient. To this end, accelerated shelf-life and microbial challenge tests were performed to assess: (i) the microbiological shelf-stability of the two sauces stabilized by heat treatments commonly applied at industrial scale to inactivate vegetative cells of spoilage microorganisms and pathogens in vegetable preserves ( F 85 7 = 2 m i n or F 95 7 = 5 m i n ); and (ii) the inhibition of Staphylococcus aureus and Bacillus cereus in the sauce with pH = ∼ 4.6 and aw < 0.92, subjected to mild pasteurization ( F 75 7 = 1 o r 2 m i n ). The results overall collected through the accelerated shelf-life tests clearly demonstrated the microbiological shelf-stability during one month of storage at thermal abuse conditions of both the novel sauces assayed; moreover, the microbial challenge tests revealed that both mild heat treatments assayed were able to inactivate S. aureus ; in addition, an inhibition of the growth of B. cereus was seen during storage at 37 °C. Results from this study are expected to be useful both from a scientific and technological standpoint, enabling efficient risk-based development of novel acidified food products.